1987
DOI: 10.1016/0378-8741(87)90055-9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of calcium channels by harmaline and other harmala alkaloids in vascular and intestinal smooth muscles

Abstract: 1 Effects of harmaline and other harmala alkaloids on the contractions induced in the vascular smooth muscle ofrabbit aorta and intestinal smooth muscle of taenia isolated from guinea-pig caecum were examined. 2 In rabbit isolated aorta, harmaline inhibited the sustained contraction induced by 65.4 mM K' with an ICo (concentration needed for 50% inhibition) of 4.6 x 10-5 M. This inhibitory effect on high K+- 4 Harmaline, at the concentrations needed to inhibit the muscle contraction, inhibited the increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…Similar to previous studies on vascular and intestinal smooth muscles (Hider et al 1981a & b;Karaki et al 1986;Shi et al 2000Shi et al & 2001, the present study demonstrate that harmine, harman, and harmaline have spasmolytic effect on carbachol-, histamine-, and KCl-induced contractions in guinea-pig tracheal smooth muscles. Since the EC 50 values for each compound to relax these 3 different spasmogens are significantly different, the mechanisms of spasmolytic action of these 3 compounds appear to be multiple.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Similar to previous studies on vascular and intestinal smooth muscles (Hider et al 1981a & b;Karaki et al 1986;Shi et al 2000Shi et al & 2001, the present study demonstrate that harmine, harman, and harmaline have spasmolytic effect on carbachol-, histamine-, and KCl-induced contractions in guinea-pig tracheal smooth muscles. Since the EC 50 values for each compound to relax these 3 different spasmogens are significantly different, the mechanisms of spasmolytic action of these 3 compounds appear to be multiple.…”
Section: Discussionsupporting
confidence: 92%
“…The present receptor binding study also suggests that inhibition of harmaline on smooth muscle Ca 2π channels is probably not due to an action on the 1,4-dihydropyridine binding site of L-type Ca 2π channels. Consistent with this result, Karaki et al (1986) showed that the inhibitory effect of harmaline on rabbit aorta and guinea-pig taenia was not reversed by Bay K 8644, a dihydropyridine which stimulates Ca 2π through L-type Ca 2π channels (Schramm et al 1983). In contrast to harmaline, harman and harmine relaxed KCl-induced contraction with higher potencies and interacted with the 1,4-dihydropyridine binding site with higher affinities.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Harmaline, at the concentrations needed to inhibit the smooth muscle contraction, has been reported to inhibit the increase of 45 Ca 2+ uptake induced by high K + , norepinephrine and carbachol in rabbit aorta and guinea pig taenia, indicating an inhibition on Ca 2+ channels of vascular and intestinal smooth muscles (26). Furthermore, the inhibitory effects of harmaline on these smooth muscles were not reversed by Bay K 8644 (26), a dihydropyridine that stimulates Ca 2+ through L-type Ca 2+ channels (27), indicating that the DHP binding site of L-type Ca 2+ channels is not involved.…”
Section: +Ecmentioning
confidence: 99%